This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
I = ∫ 0 ∞ ( 1 + x ) 2 ( 1 + x α ) d x = ∫ 0 1 ( 1 + x ) 2 ( 1 + x α ) d x + ∫ 1 ∞ ( 1 + x ) 2 ( 1 + x α ) d x = ∫ 0 1 ( 1 + x ) 2 ( 1 + x α ) d x + ∫ 0 1 ( 1 + t ) 2 ( 1 + t α ) t α d t = ∫ 0 1 ( 1 + x ) 2 d x = [ − 1 + x 1 ] 0 1 = 2 1 = 0 . 5 Transform variables to t = x 1 , d t = − x 2 d x
All these solutions are pretty nice, but for a JEE shortcut, simply put alpha=1 and solve!!!!
why 1, just put it zero
Problem Loading...
Note Loading...
Set Loading...
Relevant wiki: Integration Tricks
I = ∫ 0 ∞ ( 1 + x ) 2 ( 1 + x α ) d x = 2 1 ∫ 0 ∞ ( ( 1 + x ) 2 ( 1 + x α ) 1 + x 2 ( 1 + x 1 ) 2 ( 1 + x α 1 ) 1 ) d x = 2 1 ∫ 0 ∞ ( ( 1 + x ) 2 ( 1 + x α ) 1 + ( 1 + x ) 2 ( 1 + x α ) x α ) d x = 2 1 ∫ 0 ∞ ( 1 + x ) 2 d x = 2 1 [ − 1 + x 1 ] 0 ∞ = 2 1 = 0 . 5 Using the identity: ∫ 0 ∞ f ( x ) d x = ∫ 0 ∞ x 2 f ( x 1 ) d x